2015
DOI: 10.4238/2015.september.8.8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of E6 and E7 levels in high-risk HPV16 type cervical lesions with CCL20 and Langerhans cells

Abstract: ABSTRACT. The human papillomavirus (HPV)16 E6 and E7 correlation with chemokine ligand (CCL)20 expression and Langerhans cells (LCs) in cervical lesions was investigated. We enrolled 43 patients with surgically treated cervical lesions from the Department of Gynecology in our hospital, and 20 controls without cervical lesions. Subjects were divided by pathology: HPV16(-) and HPV16(+) normal cervical groups (N = 10 each), and HPV16(+) cervical intraepithelial neoplasia (CIN), cervical invasive carcinoma (N = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
(20 reference statements)
3
20
0
Order By: Relevance
“…Indeed, we have demonstrated that the expression of MIP-3a in the tumors was significantly associated with the number of LCs in our HNSCC patients. Similar observations have also been demonstrated in several studies of cervical cancer in which the E6 and E7 oncoproteins reduced the expression of MIP-3a in HPV-positive keratinocytes, using qPCR, ELISA, the silencing of E6 and E7 oncogenes (siRNA) and immunohistochemistry, these studies demonstrated decreases in the LC number [30][31][32].…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, we have demonstrated that the expression of MIP-3a in the tumors was significantly associated with the number of LCs in our HNSCC patients. Similar observations have also been demonstrated in several studies of cervical cancer in which the E6 and E7 oncoproteins reduced the expression of MIP-3a in HPV-positive keratinocytes, using qPCR, ELISA, the silencing of E6 and E7 oncogenes (siRNA) and immunohistochemistry, these studies demonstrated decreases in the LC number [30][31][32].…”
Section: Discussionsupporting
confidence: 64%
“…Dendritic cells represent another population of APCs that may play a role in this setting, but their contributions to the disease is less clear. Two studies reported decrease in CD1a+ DCs classified as immature DCs [73] or CD1a+ Langerhans cells [74] in the cervical stroma and/or epithelium of CIN3 and cancer patients. Other studies reported increase in CD1a+ DCs [50] , or were inconclusive due to variability in their quantification [45] .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in vitro experiments revealed that the KC-to-LC interaction mediated by E-cadherin is required for LC differentiation [65] . In HPV16-infected cervical epithelium, E6 and E7 expression and disease severity were correlated with downregulation of CCL20 expression [52] and HPV16 E6 and E7 silencing in vitro promotes CCL20 secretion and LC migration into HPV-infected epithelium [66] . Moreover, in HPV-positive HNSCC patients, immunohistochemical profiling showed that reduced CCL20 expression is correlated with a significant decrease in LC infiltration into tumors [57] .…”
Section: Impact Of Hpv Infection On Antigen Presentation To the Adaptmentioning
confidence: 94%
“…HR-HPV positive cancer cells, and E6- and E7-expressing cells can inhibit differentiation of monocytes into LCs in vitro [50] . In cervical precancerous lesions and invasive cancers, active HR-HPV infection and/or expression of E6/E7 oncoproteins were correlated with depletion of intraepithelial LCs [51] , [52] . Similarly, the expression of HPV16 E7 protein alone in murine epidermis has been associated with significantly reduced numbers of epidermal LCs [53] .…”
Section: Impact Of Hpv Infection On Antigen Presentation To the Adaptmentioning
confidence: 99%